2008
DOI: 10.1097/01.tin.0000341344.12471.eb
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Needs for Graduate Level Clinical Nutrition Education for Registered Dietitians

Abstract: Registered dietitians (RDs) took an electronic survey regarding the perceived graduate education needs and opinions on pursuing graduate degrees. A sample of 1166 RDs were surveyed. The usable response rate was 39.7%. Respondents were stratified into 3 groups for comparison. Results were reported descriptively, and χ 2 and Pearson correlation coefficients were used to test relationships. Reasons for pursuing graduate degrees included enhanced knowledge (77.2%) and personal development (61.6%). Reasons for not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, results from the 2007 Commission on Dietetic Registration (CDR) advanced practice audit suggested that narrowing the focus of advanced practice would aid in detecting an advanced practice skill set. 8 Based on ongoing interest in advanced practice and prior Academy and CDR task force and committee work, [9][10][11][12][13] CDR appointed a task force to identify advanced practice skills among RDNs who provide patient or client care. Traditionally, "clinical" patient or client care has been in acute-care settings.…”
mentioning
confidence: 99%
“…However, results from the 2007 Commission on Dietetic Registration (CDR) advanced practice audit suggested that narrowing the focus of advanced practice would aid in detecting an advanced practice skill set. 8 Based on ongoing interest in advanced practice and prior Academy and CDR task force and committee work, [9][10][11][12][13] CDR appointed a task force to identify advanced practice skills among RDNs who provide patient or client care. Traditionally, "clinical" patient or client care has been in acute-care settings.…”
mentioning
confidence: 99%